Pengembangan Media Care dalam Pembelajaran Kimia Terdiferensiasi Berbasis Kearifan Lokal - Afrina, Meydia (JOEAI (Journal of Education and Instruction), 2024)
Electrochemistry, which is taught in class XII, is a subject that is extremely closely related to phenomena that occur in everyday life. For that we need a media that is able to convey information accurately, clearly and pleasantly so that students are taught the content's notion so that they may comprehend the material on electrochemistry. Mobile learning developed is an Android-based learning media that uses smart apps creator software. This media is designed to accommodate students' diverse learning needs. The menu in mobile learning is videos, materials, virtual labs and podcasts so that it accommodates all learning styles. This study aims to determine the characteristics of chemistry application interactive (CARE) that was developed, to determine the effect of chemistry application interactive (CARE) to student activity, and to determine the effectiveness of chemistry application interactive (CARE) to improve students' scientific literacy in chemistry learning based on local wisdom. This is research and development that follows the development paradigm of analysis, design, development, implementation, and assessment (ADDIE). Data were collected by means of response questionnaires, validation questionnaires, and scientific literacy tests. The data were analyzed with the percentage that met the requirements, qualified categorization, and the N-gain test. Practitioner and student responses were highly qualified with 80.95% and 89.02%, respectively. The effectiveness experiment got 0.62 N-gain with medium category. It can be concluded that chemistry application interactive (CARE) is effective for improving students' scientific literacy on electrochemistry material based on local wisdom.